The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.3168/jds.s0022-0302(97)76169-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential to Alter the Content and Composition of Milk Fat Through Nutrition

Abstract: Nutritional manipulation of the rumen ecosystem provides a strategy to alter the content and composition of milk fat. Dietary fat supplements affect the content and composition of milk fat. The magnitude of changes is influenced by the degree of protection; as protection increases, the deleterious effects fatty acids on microbial activity decreases, and biohydrogenation of C18 unsaturated fatty acids is reduced. In addition, change is influenced by the transfer of dietary fat into milk, which is related to fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
2
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 43 publications
3
96
2
3
Order By: Relevance
“…Fats are added to dairy cattle diets to increase the energy density of diets, enhance milk yield and modify the fatty acid composition of milk fat (Murphy et al 1995;Ashes et al 1997). Fats have also been shown to depress CH 4 production (Dong et al 1997a;Machmuller and Kreuzer 1999;Dohme et al 2000).…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fats are added to dairy cattle diets to increase the energy density of diets, enhance milk yield and modify the fatty acid composition of milk fat (Murphy et al 1995;Ashes et al 1997). Fats have also been shown to depress CH 4 production (Dong et al 1997a;Machmuller and Kreuzer 1999;Dohme et al 2000).…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 99%
“…The major problem associated with excessive fat addition (more than 5-6% of the ration) is that it depresses fiber degradation in the rumen (Dong et al 1997a;Mathison et al 1998), and reduces acetate production and milk fat content (Jenkins et al 1996;Ashes et al 1997). Mathison (1997) observed that digestibility of fiber was reduced with the addition of canola oil, such that the metabolizable energy content of the diet was not different from that of the control barley-based diet.…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 99%
“…Diet composition and nutrition of dairy cows have been regarded as the most important factors that have often been utilised. The aim of the optimisation of milk fat composition has been the production of fat with more appropriate technological and/or health properties (Perdrix et al, 1996;Ashes et al, 1997).…”
mentioning
confidence: 99%
“…All tubes were gassed with CO2, tightly fitted with rubber stopper equipped with a gas release valve, and incubated at 39 ℃ for 0, 3, 6, 9, 24, or 36h. The rotating platform of the incubator (Lab-line, Environ-Melrose Park, IL) was adjusted at 175 turns min 1 -. At the end of each incubation period, tubes were withdrawn and immediately frozen.…”
Section: In Vitro Biohydrogenation Methodsmentioning
confidence: 99%
“…Whereas, only 6.0% DM was lost during the ensilage of wilted silages, distributed as 4.8% DM loss during fermentation and oxidation, 0% in effluent and 1.2% in surface waste (Mayne and Gordon, 1986). Losses of either DM during S fermentation, or soluble components in S effluent, which contains soluble carbohydrates and soluble nitrogenous compounds (McDonald et al, 1991) could have contributed to an increase in the C18:2 and C18:3 concentration of S. The DM content of typical silage effluent varies between 20 and 100 g kg 1 -DM and contains organic N, potassium, 1) The hydrogenation of C18:2 and C18:3 was described according to the equation Pt = x + y e zt -, The appearance of C18:0 was described according to the equation Pt = a + b (1 e -ct -). 2) Means within a row followed by the same letter are not different at a 0.05 level of significance by LSD multiple range test.…”
Section: Effect Of Conservation Methodsmentioning
confidence: 99%